2015
DOI: 10.9734/ajea/2015/20220
|View full text |Cite
|
Sign up to set email alerts
|

Lime-Aluminium- Phosphorus Interactions in Acid Soils of the Kenya Highlands

Abstract: PWM and CKG guided on data collection, evaluation and interpretations while author MKN was involved in data collection, data analysis, interpretation and review. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Hal ini menunjukkan bahwa pemberian dolomit saja sudah dapat meningkakan pH dan menurunkan Al dd di tanah masam sehingga meningkatkan kation-kation basa tanah walaupun tanpa pupuk anoganik dan pupuk kandang. Hal yang sama juga ditemukan oleh Agustina et al (2010), Verde et al (2013), dan Muindi et al (2015). Kapur yang larut dalam tanah akan melepas ion Ca 2+ dan Mg 2+ dan menggantikan ion H + dan Al 3+ (Kisinyo, 2016).…”
Section: Sifat Kimia Tanahunclassified
“…Hal ini menunjukkan bahwa pemberian dolomit saja sudah dapat meningkakan pH dan menurunkan Al dd di tanah masam sehingga meningkatkan kation-kation basa tanah walaupun tanpa pupuk anoganik dan pupuk kandang. Hal yang sama juga ditemukan oleh Agustina et al (2010), Verde et al (2013), dan Muindi et al (2015). Kapur yang larut dalam tanah akan melepas ion Ca 2+ dan Mg 2+ dan menggantikan ion H + dan Al 3+ (Kisinyo, 2016).…”
Section: Sifat Kimia Tanahunclassified
“…Lime enhanced the availability of more P by the Ca 2+ contained in lime displacing H + , thus resulting in a reduction in acidity implying less solubility of Al 3+ that had fixed P. This is supported by Muindi et al (2015) who found out that application of lime results in increase of soil pH and extractable P and decrease of P adsorption levels leading to replacement of hydrogen ions on the soil surface by Ca 2+ . It was found out in this study that, limed treatments of Tithonia and filter mud having 39 kg P ha -1 significantly raised the available P in both sites.…”
Section: Effect Of Treatments On Soil Available Pmentioning
confidence: 82%
“…Phosphorus sorption by soils is influenced by soil pH, ionic species in the soil solution, clay mineralogy, organic matter content, free iron and aluminium, soil calcium carbonate, temperature and time of equilibration (contact) among other factors [13,98,99,48,100].…”
Section: Factors Affecting P Sorption By Soilsmentioning
confidence: 99%
“…The dominant P ion species present in acid soils are H 2 PO 4 and PO 4 3in alkaline soils [51,101]. Adsorption of phosphorus by iron and aluminium oxides also declines with increasing pH [13,48,100] due to reduced solubility of Fe and Al ions. At lower pH, adsorption results from the reaction with iron and aluminium (reaction equation xiv) and their hydrous oxides while above pH 7.0, ions of calcium, and magnesium and their carbonates cause P precipitation (reaction equation xv) [13,48,102].…”
Section: Soil Phmentioning
confidence: 99%